Kinetics and Mechanism of Oxidation of Some Cycloalkanols by Alkaline Hexacyanoferrate(III) - K. Sati, Mukul; Singh, Pratibha; Tewary, Geeta; Mehta, S.P.S. (Asian Journal of Chemistry, 2010)
The kinetics of oxidation of cyclohexanol, cyclopentanol, cycloheptanol and cyclooctanol by alkaline hexacyanoferrate(III) was studied in the 40º-60ºC temperature range, in the absence of any catalyst. The following mechanism was suggested.